IN THE AGE OF ANALYTIC READING: Understanding Readers' Engagement With Text - Pennell, Colleen (The Reading teacher, 2014)
Teaching children to inquire, discuss ideas, and defend thinking about a literary text is a key aim of the common core state standards (CCSS). This article describes how four third-grade, male struggling readers successfully co-constructed meaning during a discussion based reading intervention rooted in philosophical inquiry. Three elements that guided reading development are closely examined: dialogic discourse, the fluidity of the text, and reader's experiential knowledge. In the age of the CCSS, considerations for transactional reading theory and dialogic teaching are discussed.